Green Structural Retrofitting Materials for Fire-Damaged Reinforced Concrete Buildings: Advances in Sustainable Repair of Distressed Buildings - Awoyera, Paul O. (2024)
One environment that hinders the performance of reinforced concrete is fire. In most cases, this results in the affected part or the entire structure being rendered useless or completely collapsing. When fire mishaps happen in structures, this is the case. This study reviews green structural retrofitting materials for reinforced concrete buildings in an effort to repair damaged structures in an environmentally friendly manner. The information gathered from earlier laboratory test results is assembled to comprehend the impact of room temperature strength properties and varied concrete mix material composition on the residual mechanical properties of concrete. The performance of various fibers, synthetic and natural, as laminate materials for concrete were evaluated, and the study showed that to a significant extent, distressed structural elements could be repaired with retrofits. However, provision of appropriate guidelines for using natural fibre laminates for retrofitting has not been overly explored. This review has highlighted areas that require further study in order to fully understand the residual strength characteristics of concrete exposed to high temperatures, particularly damaged concrete that have been retrofitted with fibers. Overall, the review's findings will be helpful to academics, professionals in the field of civil engineering, and those engaged in construction.